Modeling of gradual epidemic changes - Račkauskas, Alfredas; Tamulis, Aurelijus (Lietuvos matematikos rinkinys, 2013)
The article is devoted to analysis of epidemic changes, when transition between regimes is gradual. The consistency of CUSUM, Uniform Increments (UI) and Dyadic Increments (DI) statistics is shown. The comparison of the size-adjusted power of the tests is presented graphically.
Keywords: change point; gradual change; epidemic alternative; power analysis